Challenges and Attitudes of Iraq’s Kurdistan ESL University Students Towards Improving Oral Skills - Zubair Hamad Muhi; Innocent Nasuk Dajang (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2023)
In many instances, English language poses great challenges to English as a second language learners, obviously due to the variations between English and the learners' second language. The paper looked intensively at the challenges and attitudes of Iraq's Kurdistan English as a Second Language (ESL) University students towards improving their oral skills. The difficulties of oral skills exist in many institutions; students defied the obstacles during speaking; so, the study delved into the issues in this area. The study is quantitative. The data was collected from 63 participants selected from different institutions who utilized the survey questionnaire. The study was carried out in four educational institutions. The study used descriptive statistics and adopted tables and percentages to interpret the results. The results of this study indicated that the depression of students, apprehension, shyness, and lack of motivation made students unable to interplay with other mates in pair groups and perform activities. Teachers could not manage all activities in the classroom on their own. The results showed that lack of practice, chances, and motivation to speak in English classrooms were the most frequent obstacles for students learning to speak. Additionally, the methods and procedures employed in the lecture do not encourage students to utilize English. Thus, this study would assist university students in identifying the issues they encounter when learning to speak English and what they must do to overcome these obstacles.